Radio Frequency Identification (RFID) in supply chain management and logistics and integration with ERP software - Tomaç, Sercan (My University, 2011)
TEDARİK ZİNCİRİ YÖNETİMİ VE LOJİSTİKTE RADYO FREKANSI TANIMLAMA SİSTEMLERİ Radyo Frekansı Tanımlama (RFID), radyo dalgalarını kullanma, kişisel telsizler veya bir nesnenin tanımlama bilgilerinin (aynı olmayan seri numara formundan) sisteme transferi için kullanılan genel bir terimdir. RFID sistemi şifre çözücü (RF etiketi), kod çözücü ile veri alış verişi ve okuyuculardan meydana gelen bu üç kısımdan oluşan teknoloji sayesinde, envanter önceliklerini izleme ve nesnelerin izlenmesini kolaylaştırır. RFID tedarik zinciri yönetiminde verimlilik ve stok yönetimi gibi iş süreçleri bilgi teknolojisi organizasyon altyapısının gelişimi tabanında çalışan kablosuz sistemdir. RFID uygulamasının tedarik zinciri lojistik yönetiminde sağladıkları; profesyonel perspektif ve tecrübelerden mevcut uygulamanın durumu (avantajları ve dezavantajları) ve RFID mimarisi; RFID’nin güvenilirliği, izlenebilirliği ve izlenebilirliğinin geliştirilmesine ihtiyaç duyar. Kalite maliyetleri, en az hurda oluşma koşullarında kalite kontrolünü içerme, lojistik planlama ve kontrolünde RFID’ nin başarılı uygulaması için özel tasarım imkanı, daha iyi planlama ve kontrol olarak sıralanabilir. RFID standartları, sistemin bir bileşeninin (etiket, okuyucu veya veri bankası) efektif olarak çalışabilmesi için gereken kuralları, şartları, gereklilikleri tanımlar. Tedarik zinciri ağı üyeleri, tedarikçiler, üreticiler, dağıtıcılar, aktiviteleri hiçbir çaba sarf etmeden koordine edebilmek için birbirlerinden bağımsız olarak ve kendi gündemlerine göre çalışacaklardır. Bu tarz yönetilmeyen ağ sonuçları etkili olmamaktadır. Eylül, 2010 Sercan Tomaç

RADIO FREQUENCY IDENTIFICATION (RFID) IN SUPPLY CHAIN MANAGEMENT AND LOGISTICS Radio Frequency Identification (RFID) is a generic term that is used to describe a system that transmits the identity (in the form of a unique serial number) of an object or person wirelessly, using radio waves. It’s grouped under the broad category of automatic identification technologies [1]. RFID is a system that facilitates the tracking of objects, primarily for inventory tracking, via a threepart technology comprised of a reader, a transceiver with decoder and a transponder (RF tag). RFID is a wireless system that works in conjunction with an organization’s information technology infrastructure to improve business processes such as inventory management and efficiency in supply chain management [2]. The issues of RFID in supply chain logistics management will be given due consideration in this special issue: as a driver for a better logistics planning and control, crucial design features for the successful application of RFID in logistics planning and control, implication for quality control in terms of less scrap and quality costs, the RFID architecture needed to improve tracking and tracing, and reliability of RFID and the current status (advantages and disadvantages) of application from practitioners’ perspective and experiences. Supply chain management is the combination of process and information technology to integrate the members of the supply chain into a whole. Supply chain managers already have many tools to wield at these problems. RFID will be a new tool and offer an unprecedented ability for supply chain members to coordinate their activities. In managing supply chains, the information collected by RFID networks will become inputs to the fundamental decisions like; location, production, inventory, transportation. September, 2010 Sercan Tomaç
Keywords: Endüstri Mühendisliği; Lojistik Yönetimi; Radyo Frekansı ile Tanımlama Sistemleri (RFID); Tedarik Zinciri Yönetimi